The Effect of Winding Yarn (Just In Time) on Winding Machine Productivity - Noorzaman, Sandi; Hidayat, Rachmat (Jurnal Logistik Indonesia, 2023)
An appropriate production system (just in time) is a concept that supports cost management to anticipate changes that occur in the industrial environment due to advances in technology and automation. In the just-in-time concept, production is carried out through a certain amount of inventory (inventory equals 0). This elimination of inventory amounts automatically eliminates carrying and other costs, leading to a decrease in tolerance levels for product errors. The aim of this research is to find out and examine the influencing factors of input and output, just in time simultaneously which have a significant influence on production machines effectively and efficiently at PT. Asindo, and to find out and research the dominant influencing factors of just in time on production machines effectively and efficiently at PT. Asindo. The results of the analysis show that the first hypothesis proposed in this research is that just-in-time production factors simultaneously have a significant influence on effective and efficient production machines at PT Asindo. This is supported by the results of the t-test, where the results show thatof (19.75) > t table of (2.03693). By looking at the value of R square = R=0.96135, meaning that the up-down variation of variable Y (effective and efficient production machines at PT. Asindo) is 92.419%, influenced by the independent variables in the model and the remaining 7.581% is due to other factors not included in this analysis. This means that the contribution of machine productivity in this model is good because it is more than 50%. From a series of design activities to achieve high production volumes with minimum inventory or minimum defective products for production and finished products, where the winding machine in production only produces output according to demand requirements.